2017
DOI: 10.1007/s12035-016-0347-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dysregulated miRNA in Peripheral Blood Mononuclear Cells from Ischemic Stroke Patients

Abstract: Epigenetic modification may play an important role in pathophysiology of ischemic stroke (IS) risk. MicroRNAs (miRNAs), which constitute one of the modes of epigenetic regulation, have been shown to be associated with a number of clinical disorders including IS. The purpose of this study was to investigate the miRNA profile in the peripheral blood mononuclear cells (PBMCs) of IS patients and compare it with stroke-free controls. Blood samples were obtained from 19 healthy age-gender-race matched individuals wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…MicroRNAs (miRNAs) regulate cellular pathways in a variety of clinical disorders, including ischemic stroke [7]. miR-137 is enriched in the brain and negatively regulates cell proliferation and accelerates the neuronal differentiation of embryonic neural stem cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) regulate cellular pathways in a variety of clinical disorders, including ischemic stroke [7]. miR-137 is enriched in the brain and negatively regulates cell proliferation and accelerates the neuronal differentiation of embryonic neural stem cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomal miRNAs establish the communication between cell-to-cell and are involved in regulating different biological processes via modulating the expression of target genes. Notably, the critical role of exosomal miRNAs in the development of stroke is emerging [ 17 , 19 , 25 ]. Recent study showed that the plasma exosomal miR-422a and miR-125b-2-3p were potential blood-base biomarkers for monitoring and diagnosing of IS patients [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bam et al investigated IS patients in the first 48 h and found several miRNAs to be dysregulated that are common in our RAA group, including hsa-miR-199b-3p, − 223, −30e, − 503, and − 550*. Among the top pathways enriched for regulated miRNAs were those related to cancer, hematological, and immunological diseases [15]. Additionally, Jickling et al analyzed miRNA expression in acute IS patients and found 8 differentially expressed miRNAs that potentially regulate genes in pathways associated with inflammatory/immune responses [16].…”
Section: Discussionmentioning
confidence: 65%